Genetic analysis of trends in production and reproduction traits over years using regression methods in Sahiwal cows - PARVEEN, KAISER; GUPTA, A K; GANDHI, R S; CHAKRAVARTY, A K; MUMTAZ, SHABAHAT (The Indian Journal of Animal Sciences, 2018)
The present study was conducted on first lactation performance records of 820 Sahiwal cows maintained at NDRI, Karnal spread over 54 years (1962–2015) to study the effect of genetic and non-genetic factors on production and reproduction traits, to estimate genetic parameters and the genetic trends by different methods. The traits considered were age at first calving (AFC), first lactation 305 days milk yield (FL305DMY), first lactation total milk yield (FLTMY), first lactation length (FLL) and first calving interval (FCI). The effect of genetic and non–genetic factors like sire, month of birth/calving, period of birth/calving, AFC group and first service period group on normalized production and reproduction traits was assessed by GLM function of Statistical Analysis System (SAS Institute Inc., version 9.2). Paternal half sib correlation method was used to estimate the heritability of different characters. Phenotypic trend per year was estimated as the linear regression of the phenotypic value (P) on time (year).The genetic trend were estimated by Smith I, Smith II, BLUP (Sire Model), BLUP Animal Model methods respectively. The effect of sire was significant for all traits except calving interval. Effect of month was significant for all the traits except for FLTMY. Effect of period was significant for all the traits except FCI. Effect of AFC group was not significant on FCI. The heritability estimates of AFC, FL305DMY, FLTMY, and FLL were 0.45±0.14, 0.18±0.11, 0.19±0.10, 0.16±0.09, respectively. The repeatability estimate for FL305DMY was 0.45±0.17. The phenotypic trend of FL305DMY, FLTMY, FLL, AFC and FCI was –19.85±2.17 kg, –26.06±2.4 kg, –3.22±0.26 days, –0.05±0.31days and 0.041±0.47 days respectively per year and were statistically significant. Genetic trends were positive, significant and in desirable direction in production traits. Regression methods used for the estimation of genetic trends BLUP (Sire Model), BLUP Animal Model are superior to traditional methods because of small standard error. Low magnitude of genetic trend and unfavorable environmental trends indicated the need to increase herd size and improvement in managemental practices. Thus, dairy genetic improvement programmes needed to be redesign appropriate strategies that would be more beneficial to the currently changing scenarios.